2021
DOI: 10.33258/birci.v4i2.1980
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of E-Service Quality on Satisfaction and Its Impact on Customer Loyalty of Mobile Banking Users (Case Study of Bank Syariah Mandiri KCP Belawan)

Abstract: Bank Syariah Mandiri (BSM) is a real example of a bank that has utilized information technology as an additional service provided to improve the customer experience in transacting online via the internet, namely through a mobile banking application. The application of mobile banking is one form of BSM's commitment in providing good quality electronic services, and can be felt and assessed by customers who have used it. These assessments can then affect their level of satisfaction. Based on this, it then encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 2 publications
2
13
0
1
Order By: Relevance
“…According to the first hypothesis (H1), E-service quality affects E-satisfaction. Several prior studies (Nasution et al, 2019;Marliyah et al, 2021;Indriastuti et al, 2022;Pradnyadewi & Giantari, 2022) that found that digital service quality positively affects customer satisfaction support this hypothesis. According to the second hypothesis (H2), E-satisfaction affects E-loyalty.…”
Section: Literature Reviewmentioning
confidence: 74%
See 2 more Smart Citations
“…According to the first hypothesis (H1), E-service quality affects E-satisfaction. Several prior studies (Nasution et al, 2019;Marliyah et al, 2021;Indriastuti et al, 2022;Pradnyadewi & Giantari, 2022) that found that digital service quality positively affects customer satisfaction support this hypothesis. According to the second hypothesis (H2), E-satisfaction affects E-loyalty.…”
Section: Literature Reviewmentioning
confidence: 74%
“…According to the second hypothesis (H2), E-satisfaction affects E-loyalty. Previous studies (Nasution et al, 2019;Marliyah et al, 2021;Indriastuti et al, 2022;Pradnyadewi and Giantari (2022)) show how customer satisfaction affects customer loyalty in the context of digital services support this claim. According to the third hypothesis (H3), e-loyalty is also influenced by e-service quality.…”
Section: Literature Reviewmentioning
confidence: 75%
See 1 more Smart Citation
“…Emphasises the positive impact of innovative learning media, such as Quizizz, on stimulating students' interest in learning, particularly in the context of rapid technological development (Rulismi et al, 2023b). Overall, this study contributed to the growing body of literature on educational technology by providing empirical evidence of Quizizz's effectiveness as a learning tool in Vocational High Schools (Marlizar et al, 2021). Nevertheless, future research endeavors should persist in delving into the nuanced impacts of gamified learning platforms such as Quizizz.…”
Section: Challenges and Limitationsmentioning
confidence: 81%
“…Pengembang perlu memperhatikan setiap dimensi kualitas layanan elektronik seperti ketersediaan informasi, kemudahan penggunaan, privasi/keamanan, gaya grafis, dan keandalan. Dengan demikian, aspek kenyamanan fitur dan tampilan fitur yang menarik menjadi faktor terpenting dalam membangun loyalitas online dan kepuasan online melalui kualitas layanan elektronik yang disediakan (Marliyah et al, 2021).…”
Section: ) Meningkatkan Kualitas Layanan Elektronik Dalam Mempengaruh...unclassified